Assessment of Post Exposure Prophylaxis (PEP) in Omdurman Voluntary Counselling and Testing Center (OVCTC) - MANSOUR, MUSA Basheer; Ahmedana, Sara Elsheikh (Jour Med Resh and Health Sci, 2020)
PEP is taking human immunodeficiency virus medicine (HIV) within 72 hours after possible exposure to HIV to prevent the occurrence of the disease. Significance: exposure to the needle, surgical equipment, and rape is a life-threatening condition for hepatitis B virus (HBV), hepatitis C virus (HCV), HIV, acquired immunodeficiency syndrome (AIDS) infection, tetanus, and syphilis. The objective of this study was to assess the PEP. Methods: It was a descriptive-analytical study in OVCTC in September 2008. 30 patients in study as the whole number. We included all patients attending the OVCTC and potential exposed either occupationally or through sexual intercourse and received antiretroviral therapy (ARV) agents as prophylaxis All cases diagnosed as HIV/AIDS and all persons need counseling were excluded in this study. Secondary data were collected from the records of the patients in OVCTC. Ethical considerations and clearance were taken from OVCTC and patients. It was accepted by the director. Results: In these study 30 cases fully described from the record and part of them were interviewed. Most cases (13) 43% in the age group 26 -35 years and the minority (2) 6% in age group (5 -15 years) and (2) 6% in age group (46-55years). Male (17)56.6% and Female (13)43.4%. Single (14) 46.6%, married (14)46.6%, widow (1)3.3% and divorced (1)3.3%. Most of them (21),70% are the health care professional, (27) 90% are educated and (26)86.3%lived in Khartoum. The equipment of exposure (28)93.3% due to needle stick, (1)3.3% due to rape and (1)3.3% due to rosary. (16)53.3%were expose in 2007, (12)40% in 2008 and (2)6.6% in 2006. All of them started needle stick protocol. The baseline of HIV testing is negative in all. All of them started Duovir according to world health organization guidelines and non-reported side effects or complications. Conclusion: Although PEP is offered in OVCTC according to world health organization (WHO) guidelines, pre and post-test counseling, ARV prophylaxis, and counseling including ARV side effects; the outcome is good, although the patients are not adherent to schedule follow-up in the center.